Endoscopic radiofrequency ablation or surveillance in patients with Barrett's oesophagus with confirmed low-grade dysplasia: a multicentre randomised trial. Issue 6 (8th March 2021) - Barret, Maximilien; Pioche, Mathieu; Terris, Benoit; Ponchon, Thierry; Cholet, Franck; Zerbib, Frank; Chabrun, Edouard; Le Rhun, Marc; Coron, Emmanuel; Giovannini, Marc; Caillol, Fabrice; Laugier, René; et al.
Abstract : Objective: Due to an annual progression rate of Barrett's oesophagus (BO) with low-grade dysplasia (LGD) between 9% and 13% per year endoscopic ablation therapy is preferred to surveillance. Since this recommendation is based on only one randomised trial, we aimed at checking these results by another multicentre randomised trial with a similar design. Design: A prospective randomised study was performed in 14 centres comparing radiofrequency ablation (RFA) (maximum of 4 sessions) to annual endoscopic surveillance, including patients with a confirmed diagnosis of BO with LGD. Primary outcome was the prevalence of LGD at 3 years. Secondary outcomes were the prevalence of LGD at 1 year, the complete eradication of intestinal metaplasia (CE-IM) at 3 years, the rate of neoplastic progression at 3 years and the treatment-related morbidity. Results: 125 patients were initially included, of whom 82 with confirmed LGD (76 men, mean age 62.3 years) were finally randomised, 40 patients in the RFA and 42 in the surveillance group. At 3 years, CE-IM rates were 35% vs 0% in the RFA and surveillance groups, respectively (p<0.001). At the same time, the prevalence LGD was 34.3% (95% CI 18.6 to 50.0) in the RFA group vs 58.1% (95% CI 40.7 to 75.4) in the surveillance group (OR=0.38 (95% CI 0.14 to 1.02), p=0.05). Neoplastic progression was found in 12.5% (RFA) vs 26.2% (surveillance; p=0.15). The complication rate was maximal after the first RFA treatment (16.9%). Conclusion: RFA modestly reduced the prevalence of LGD as well as progression risk at 3 years. The risk-benefit balance of endoscopic ablation therapy should therefore be carefully weighted against surveillance in patients with BO with confirmed LGD. Trial registration number: NCT01360541 .